Comparative studies in education: new theoretical and methodological approaches - doi: 10.4025/actascieduc.v36i1.19012 - Elma Júlia Gonçalves de Carvalho (Acta Scientiarum: Education, 2014)
Comparative methodology is an extremely rich analytic tool in educational systems. Since it identifies similar and different issues, it broadens the field of analysis and understanding on the national reality when contrasted to that of other countries, especially with their public policies and their administration of education. Several theoretical and methodological issues on comparative studies are historically investigated and the new perspectives on current comparative education are indicated. Current research demonstrates that the production of a new paradigmatic perspective, highlighting the rejection of traditional national frontiers as the only or the main categories of analysis, is on the increase. On the one hand, the above-mentioned perspective invites experts to adopt international references in the analysis of educational systems and policies and, on the other hand, makes them aware of regional differences and provides them with new horizons for their investigation.